Study on toxic chemicals in Kuantan river during pre and pst monsoon season - Rahman, Md. Mokhlesur; Awang, Mohamed; Yunus, Kamaruzzaman (INSI Publications, 2013)
A study on water quality based on toxic heavy metals was carried out between October,2010 and January, 2011 at Kuantan River, Pahang. Three stations expected to be polluted were chosen to be studied in this study. The stations were firstly, the area near to the fish landing jetty, secondly the area adjacent to Hospital Tengku Ampuan Afzan, Kuantan and thirdly at the Kuantan River estuary. In-situ measurements were conducted and samples were also collected during low tides for laboratory analysis. The results of this study showed that the metalloid such as arsenic ranged from 5.05 to 32.09 ug/L during pre-monsoon and from 5.71 to 22.81 ug/L during post-monsoon. The two highest quantity of heavy metals found were copper ranging from 2.66 to 26.27 ìg/L and zinc from 6.02 to 38.61 ug/L for pre-monsoon season. During the post-monsoon season, copper ranged from 18.03 to 90.79 ug/L and zinc from 3.42 to 11.34 ug/L. The values for other heavy metals were low compared to these two. Results of this study shows that the Kuantan River can be classified under Class 2 based on the Interim National Water Quality Standards (INQWS) classification which indicates that it is not heavily polluted. The study revealed that seasonal changes and human activities had affected the quality of water in the river.